A Universal Approach to Aqueous Energy Storage via Ultralow‐Cost Electrolyte with Super‐Concentrated Sugar as Hydrogen‐Bond‐Regulated Solute. Issue 16 (4th March 2020) - Bi, Haibo; Wang, Xusheng; Liu, Haili; He, Yonglin; Wang, Weijian; Deng, Wenjun; Ma, Xinlei; Wang, Yushu; Rao, Wei; Chai, Yuqiao; Ma, Hui; Li, Rui; et al.
Abstract: Aqueous energy‐storage systems have attracted wide attention due to their advantages such as high security, low cost, and environmental friendliness. However, the specific chemical properties of water induce the problems of narrow electrochemical stability window, low stability of water–electrode interface reactions, and dissolution of electrode materials and intermediate products. Therefore, new low‐cost aqueous electrolytes with different water chemistry are required. The nature of water depends largely on its hydroxyl‐based hydrogen bonding structure. Therefore, the super‐concentrated hydroxyl‐rich sugar solutions are designed to change the original hydrogen bonding structure of water. The super‐concentrated sugars can reduce the free water molecules and destroy the tetrahedral structure, thus lowering the binding degree of water molecules by breaking the hydrogen bonds. The ionic electrolytes based on super‐concentrated sugars have the expanded electrochemical stability window (up to 2.812 V), wide temperature adaptability (–50 to 80 °C), and fair ionic conductivity (8.536 mS cm −1 ). Aqueous lithium‐, sodium‐, potassium‐ion batteries and supercapacitors using super‐concentrated sugar‐based electrolytes demonstrate an excellent electrochemical performance. The advantages of ultralow cost and high universality enable a great practical application potential of the super‐concentrated sugar‐based aqueous electrolytes, which can also provide great experimental and theoretical assistance for further research in water chemistry. Abstract : Super‐concentrated sugars are used to regulate the hydrogen bond of water by breaking its fully hydrogen‐bonded structure in ultralow‐cost ionic electrolytes, with the positive effects of an expanded electrochemical stability window, very low freezing point, and fair ionic conductivity. Universal performance improvements are realized in the aqueous energy‐storage systems using the super‐concentrated sugar‐based electrolytes.